Histological analysis of cleaning capacity in apical third of flattened root canals with passive ultrasonic irrigation - Tiago Luís Boff; Caroline Zamin; Deborah Meirelles Cogo; José Roberto Vanni; Mateus Silveira Martins Hartmann; Volmir João Fornari (Revista Sul-Brasileira de Odontologia, 2015)
The aim of this study was to evaluate histologically the passive use of ultrasound for cleaning the apical portion of flattened root canal systems. Material and methods: The sample consisted of 20 extracted human mandibular incisors which were divided into two groups after being prepared with the rotary system Hero 642 up to size #45 surgical diameter: Group A – final irrigation with 4 ml of 2.5% sodium hypochlorite by the conventional technique using a syringe, and Group B – final irrigation with 4 ml of 2.5%, sodium hypochlorite divided into 1 ml amounts which were activated with the passive use of ultrasound for 15 seconds each time, generating a total activation period of 1 minute. Following, the teeth were subjected to morphometric analysis to evaluate the cleaning ability promoted in both groups. Results and Conclusion: Statistical analysis showed significant difference (p < 0.05) between the groups, with the passive ultrasonic irrigation resulting in cleaner canals.